Uloha endotelu a oxidu dusnatého v regulácii cievneho tonusu - Púzserová, A; Kopincová, J; Bernátová, I (Ceskoslovenska fysiologie, 2008)
Vascular system is a large complex of tubes with different diameters which are able to perceive changes of endogenous milieu, to integrate and modulate signals of intercellular communication and to respond and adapt by a local production of different kinds of mediators affecting vascular structure and function. For a long time, it has been assumed that the main determinant of vasomotor function was the nervous system and the monolayer of endothelial cells was only a physical barrier between the vessel wall and blood. However, the first publications in 1960s and 70s indicated that endothelium is not only a passive barrier. Endothelium features autocrine, paracrine and endocrine activities. Vascular endothelium plays an important role in the regulation of vascular tone, blood pressure and blood flow beside central regulation of nervous system. The existence of endothelium-derived relaxing factor (EDRF) was found out by Furchgott and Zawadzki (1980) who showed that acetylcholine induced relaxation of the rabbit aorta only in the presence of intact endothelium. Nowadays, nitric oxide (NO), previously known as EDRF, is considered one of the crucial endothelium-derived vasorelaxing substances participating in the regulation of basal vascular tone, vascular resistance and thus in the regulation of blood pressure. Arterial bed is dilated continuously as a consequence of constant production of NO. Any damage of endothelium modifies regulatory functions of endothelial cells. These conditions are characterised as endothelial dysfunction associated with imbalance between vasodilating and vasoconstricting factors, pro- and anticoagulation factors and factors stimulating and inhibiting growth and proliferation of cells. However, cellular mechanisms which are involved in the development of endothelial dysfunction, are still not well-known.
Keywords: krevní tlak; Animals; Vasodilation; cévní endotel; oxid dusnatý; Vasoconstriction; lidé; zvířata; vazodilatace; Blood Pressure; Endothelium, Vascular; vazokonstrikce; Nitric Oxide; Humans